2011
DOI: 10.4049/jimmunol.1101568
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Mutational and Transcriptional Enhancers in Ig Genes

Abstract: Secondary immunoglobulin (Ig) gene diversification relies on activation-induced cytidine deaminase (AID) to create U:G mismatches that are subsequently fixed by mutagenic repair pathways. AID activity is focused to Ig loci by cis-regulatory DNA sequences named targeting elements. Here we show that in contrast to prevailing thought in the field, the targeting elements in the chicken IGL locus are distinct from classical transcriptional enhancers. These mutational enhancer elements (MEEs) are required over and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…These studies imply that transcription driven by any promoter might support SHM. This notion is consistent with later studies suggesting that the level of transcription is not necessarily correlated with the level of mutations [80, 81]. It has been long proposed that the mutator enzyme (now known as AID) may associate with RNAP II to mediate SHM [82].…”
Section: Cis Regulatory Elements In Shm Targetingsupporting
confidence: 88%
“…These studies imply that transcription driven by any promoter might support SHM. This notion is consistent with later studies suggesting that the level of transcription is not necessarily correlated with the level of mutations [80, 81]. It has been long proposed that the mutator enzyme (now known as AID) may associate with RNAP II to mediate SHM [82].…”
Section: Cis Regulatory Elements In Shm Targetingsupporting
confidence: 88%
“…Importantly, this DIVAC ( div ersification ac tivator) region includes, but is not limited to, the defined IgL enhancer, which was previously shown not to be required for SHM in the IgL locus (9, 29). The identity of the functionally critical elements, however, is in dispute (9, 25), and thus far, no specific collection of DNA binding sites has been identified that can explain DIVAC function (24, 27). …”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, all of the studies of the DT40 IgL locus have narrowed in on regions containing E boxes (9, 25, 28). The E box motif is defined by the consensus sequence CANNTG, and serves as a binding site for class I helix-loop-helix DNA binding proteins, or E proteins, which have well characterized roles in B and T lymphocyte development (30).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, deletion of this region in the Igh locus diminishes Pol II and ablates Spt5 and AID recruitment (8, 31). In DT40 cells, deletions in this region in the Igλ locus modulate transcription and reduce mutagenesis (3234). Thus, a definitive role for the 3′ enhancer region in transcription and mutation is unclear at this time.…”
Section: Discussionmentioning
confidence: 99%